(untitled) (Agroindustrial Science, 2026)
Ecuadorian cocoa is a pillar of the national economy, although its quality can be compromised by the presence of mycotoxin-producing fungi during fermentation and storage. The main objective of this study was to identify the fungal strains present in fermented cocoa beans using morphological markers in four collection centers in the Bolívar canton. One hundred and fifty beans per center were collected in the last phase of fermentation, which were seeded in DG18 medium and incubated at 25°C. The developed colonies were evaluated by macroscopic and microscopic observations, supported by taxonomic keys. Sixty-four fungal strains with wide variability in texture, coloration, and exudate were isolated and characterized. Microscopic analysis identified two predominant genera: Aspergillus spp. and Penicillium spp., with Aspergillus being the most abundant in all collection centers. Statistical analysis showed significant differences in fungal load between centers (p < 0.05), reflecting the influence of fermentation and storage practices on microbial diversity. Ultimately, the identification of these genera highlights the need to implement rigorous controls in post-harvest management, given that species of the Aspergillus Nigri section can produce ochratoxin A, compromising the safety of cocoa.